A microfluidic electrochemical cell for studying the corrosion of uranium dioxide (UO2). Issue 30 (4th July 2022) - Yao, Jennifer; Lahiri, Nabajit; Tripathi, Shalini; Riechers, Shawn L.; Ilton, Eugene S.; Chatterjee, Sayandev; Buck, Edgar C.
Abstract : Highlight of the multimodal characterization of corrosion behaviour of microgram quantities of UO2, enabled by a novel particle-attached microfluidic electrochemical cell. Abstract : We have developed a specialized microfluidic electrochemical cell that enables in situ investigation of the electrochemical corrosion of microgram quantities of redox active solids. The advantage of downscaling is the reduction of hazards, waste, expense, and greatly expanding data collection for hazardous materials, including radioactive samples. Cyclic voltammetry was used to monitor the oxidation–reduction cycle of minute quantities of micron-size uraninite (UO2 ) particles, from the formation of hexavalent uranium (U(vi )), U3 O7 and reduction to UO2+ x . Reaction progress was also studied in situ with scanning electron microscopy. The electrochemical measurements matched those obtained at the bulk-scale and were consistent with ex situ characterization of the run products by X-ray photoelectron spectroscopy, scanning transmission electron microscopy, and atomic force microscopy; thus, demonstrating the utility of the microfluidic approach for studying radioactive materials.